Efflux Pump Blockers in Gram-Negative Bacteria: The New Generation of Hydantoin Based-Modulators to Improve Antibiotic Activity - Otręebska-Machaj, Ewa; Chevalier, Jacqueline; Handzlik, Jadwiga; Szymańska, Ewa; Schabikowski, Jakub; Boyer, Gérard; Bolla, Jean-Michel; Kieć-Kononowicz, Katarzyna; Pagès, Jean-Marie; Alibert, Sandrine (Frontiers in Microbiology, 2016)
Multidrug resistant (MDR) bacteria are an increasing health problem with the shortage of new active antibiotic agents. Among effective mechanisms that contribute to the spread of MDR Gram-negative bacteria are drug efflux pumps that expel clinically important antibiotic classes out of the cell. Drug pumps are attractive targets to restore the susceptibility towards the expelled antibiotics by impairing their efflux activity. Arylhydantoin derivatives were investigated for their potentiation of activities of selected antibiotics described as efflux substrates in Enterobacter aerogenes expressing or not AcrAB pump. Several compounds increased the bacterial susceptibility towards nalidixic acid, chloramphenicol and sparfloxacin and were further pharmacomodulated to obtain a better activity against the AcrAB producing bacteria.